Monte Carlo simulation of coherent effects in multiple scattering - Meglinski, Igor V.; Kuzmin, Vladimir L.; Churmakov, D. Y.; Greenhalgh, Douglas A. (Royal Society, 2005)
Using a combination of the stochastic Monte Carlo technique and the iteration procedure of the solution to the Bethe-Salpeter equation, it has been shown that the simulation of the optical path of a photon packet undergoing an nth scattering event directly corresponds to the nth-order ladder diagram contribution. In this paper, the Monte Carlo technique is generalized for the simulation of the coherent back-scattering and temporal correlation function of optical radiation scattered within the randomly inhomogeneous turbid medium. The results of simulation demonstrate a good agreement with the diffusing wave theory and experimental results.
Keywords: Bethe-Salpeter Equation; Coherent Back-Scattering; Temporal Field Correlation Function; Diffusing-Wave Spectroscopy; Monte Carlo Simulation